Psychiatric comorbidity among elderly inpatients admitted to a regional geriatric center in Northeast India: a cross-sectional study - Mazumdar, Suranjita; Phookun, H. R. (International Journal Of Community Medicine And Public Health, 2026)
Background: Psychiatric disorders frequently coexist with medical illnesses in elderly patients and often remain under-recognized, adversely affecting treatment outcomes and recovery. The aim of this study was to estimate the prevalence and pattern of psychiatric morbidity among elderly inpatients admitted to a Regional Geriatric Centre and to examine the relationship with socio-demographic characteristics and cognitive status. Methods: This hospital-based cross-sectional study was conducted over one year (August 2016-July 2017) among 85 consecutive inpatients aged ≥60 years admitted to a tertiary care geriatric center in Northeast India. Diagnoses were made using ICD-10 criteria, supported by mini-mental state examination (MMSE) and brief psychiatric rating scale (BPRS). Data were summarized using descriptive statistics. Results: Psychiatric morbidity was present in 40 (47.1%) participants. Depression was the most common disorder (40%), followed by dementia (20%) and substance use disorders (20%). Cognitive impairment was observed in a substantial proportion of patients with psychiatric morbidity. Psychotic symptoms were present in 10 (11.76%) participants. Conclusions: Nearly half of elderly inpatients had psychiatric co-morbidity, with depression and cognitive disorders being predominant. Routine screening and early psychiatric intervention may improve outcomes in geriatric inpatient care.